2016
DOI: 10.1080/0067270x.2016.1173302
|View full text |Cite
|
Sign up to set email alerts
|

Poison arrows and bone utensils in late Pleistocene eastern Africa: evidence from Kuumbi Cave, Zanzibar

Abstract: Most of our current knowledge of late Pleistocene African bone technology is drawn from southern African sites, with recent discoveries indicating that bone-and stone-tipped arrows (propelled by a bow) were in use prior to 60,000 years BP. Integration of archaeological with ethnographic data similarly suggests that hunting with poison-tipped arrows on the African continent has an antiquity of at least 24,000 years. Unfortunately, similar analysis of material from eastern Africa is largely absent and consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 82 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…We present our results by phase below. Specialist reports on the long-term cave and landscape evolution (Kourampas et al 2015), bone tools (Langley et al 2016) and fauna can be found elsewhere.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We present our results by phase below. Specialist reports on the long-term cave and landscape evolution (Kourampas et al 2015), bone tools (Langley et al 2016) and fauna can be found elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…The only cultural materials recovered from this deposit were two pieces of worked bone. One is a point, the form of which is akin to those from the Phase 3 layers, while the other is a notched piece of bovid upper limb bone (Langley et al 2016). Both these items show signs of having been worked by stone tools (Langley et al 2016), so their absence from the assemblage would seem to reflect changing site use in the vicinity of our excavation area, rather than technological change.…”
Section: Phase 2: Terminal Pleistocene Lsa Occupationmentioning
confidence: 99%
See 2 more Smart Citations
“…Other behaviorally significant artifact types at some Middle and Later Stone age sites in East Africa. (a) Ostrich eggshell beads and production debris, spit XVII, Kisese II; (b) ochre‐stained “palette” or lower grindstone, spit III, Kisese II; (c) ochre fragment with grinding facets and striations, spit VI, Kisese II; (d) notched/incised bone projectile point, context 1015, Kuumbi Cave; (e) gastropod and sea shell ( Conus ) beads, layers 4–16, Panga ya Saidi; (f, g) upper grindstones, bed V, Mumba . Copyright from University of Tübingen (h) notched or incised bone fragment, layer 8, Panga ya Saidi.…”
Section: Introductionmentioning
confidence: 99%